The risk of eating disorder relapse during pregnancy and after delivery and postpartum depression among women recovered from eating disorders - Mariko Makino; Mitsuo Yasushi; Sueharu Tsutsui (BMC, 2020)
Abstract Background Studies have shown that women of reproductive age develop eating disorders (EDs). Few studies have examined EDs in women by performing long-term follow-ups during pregnancy and after delivery. Our study aimed to identify relapse of EDs during pregnancy and after delivery as well as postpartum depression in women who had complete remission of EDs. Methods Of the 1008 patients with EDs who visited our outpatient clinic between 1994 and 2004, 55 experienced ED remission and pregnancy. Of these, 25 (21 with BN and 4 with AN) consented to participate in this study. Finally, 24 patients were included in this study after 1 patient was excluded owing to a miscarriage. They were interviewed every 2 weeks both during pregnancy and after giving birth. We used the Eating Attitudes Test-26 (EAT-26) and Edinburgh Postnatal Depression Scale (EPDS) as reference scales for diagnosing the EDs and the postpartum depression, respectively. We used a two-sided unpaired test for the statistical analysis. Results Sixteen participants (67%) experienced ED relapse during pregnancy and twelve (50%) relapsed after birth. Twelve (50%) had postpartum depression, four of whom (33%) had low-birth-weight infants. Among the participants who did not have postpartum depression, there were no low-body-weight infants. There was no significant difference (p = 0.065) in birth weight between the postpartum depression and non-depression groups. Conclusions Our study revealed that recurrence of EDs and the occurrence of postpartum depression were higher in this population, indicating the need to closely monitor EDs both during pregnancy and after birth.